The Chinese Inventory of Psychosocial Balance Short-Form Questionnaire for the Older Adults: Validity and Reliability Study - Chen, Pei-Yun; Ho, Wen-Chao; Lo, Chyi; Yeh, Tzu-Pei (Frontiers in Psychology, 2022)
Background: Drawing from Erikson’s theory, Domino and Affonso [1] constructed the Inventory of Psychosocial Balance (IPB)—a scale with satisfactory reliability and validity [1]. However, the lack of a credible Chinese version of the scale may hinder research on ego development in Taiwan. The aim of the present study was to constructed a short form Chinese IPB. In addition, factor analysis was employed to shorten the original 120-item scale to make it suitable for application in the older adults in the future. Methods: The study involved three steps: The first step was to establish the 120-items Chinese Inventory of Psychosocial Balance(C-IPB) and we conducted translation, back-translation, expert validity, and reliability of pilot study for the step. Following the first step was to construct the short-form C-IPB(CIPB-SF) in the second step and the CIPB-SF was developed via item analysis and factor analysis. Finally, we assessed the reliability and validity of the CIPB-SF via structural equation model in the third step. Results: Three hundred eight older adults without cognitive disorder completed the IPB. The 40-item CIPB-SF was completed through item analysis and factor analysis. The internal consistency test of CIPB-SF and the eight stages were well (Cronbach's α= 0.81 to 0.89). The CIPB-SF had acceptable validity, except in the intimacy and identity stages, in which validity was only fair. Compared with the IPB, the CIPB-SF had good reliability and acceptable validity. However, because of its conciseness, the 40-item CIPB-SF was more suited for application among the Chinese elderly population because its application avoids physical overload. Conclusions: The CIPB-SF served as a concise scale for assessing ego development in our study. This scale can also serve as a useful tool for convenient screening in the future Key word: ego development, life span, validity, reliability, elderly